Trajectory Planning Optimization of Two-degree-of-freedom Parallel Mechanism - Junwei Shen; Heng Cheng (Jixie chuandong)
Aiming at the vibration problem of traditional parallel manipulator trajectory planning， two-degree-of-freedom parallel mechanism is studied， and a trajectory planning method based on high-order differentiable compound polynomial is proposed. Firstly， a planar two-degree-of-freedom parallel manipulator for product packaging is designed， and the inverse kinematics and forward kinematics are analyzed. The model is built by Solidworks software， and the correctness of kinematics analysis is verified. According to the physical boundaries and industry needs， the appropriate workspace is selected. Then， a new compound polynomial is generated by combining cubic polynomial with Bessel curve. Finally， the prototype of the manipulator is made and tested in practice. The research results show that， compared with cubic polynomial， the position， velocity and acceleration curves of the trajectory generated by the new polynomial are smoother in the same duration， which effectively reduces the vibration of the mechanism， reduces the maximum velocity and acceleration by about 40%， and effectively prolongs the mechanical life.